The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/adfm.202206301
|View full text |Cite
|
Sign up to set email alerts
|

How to Select Phase Change Materials for Tuning Condensation and Frosting?

Abstract: Synthetic surfaces engineered to regulate phase transitions of matter and exercise control over its undesired accrual (liquid or solid) play a pivotal role in diverse industrial applications. Over the years, the design of repellant surfaces has transitioned from solely modifying the surface texture and chemistry to identifying novel material systems. In this study, selection criteria are established to identify bio-friendly phase change materials (PCMs) from an extensive library of vegetable-based/organic/esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…We tested other materials (aluminum, stainless steel, poly-tetrafluoroethylene) also, and consistently observed adhesive failure, yielding IAS values consistent with literature reports, thereby validating the reliability of our test setup and adopted protocol. 12,13 Next, we replaced pure water with 1 wt% sodium chloride aqueous solution and froze it on the copper surface under the same conditions, and repeated the experiments to obtain IAS. Here, weight percentage refers to the mass ratio of the contaminant ( e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested other materials (aluminum, stainless steel, poly-tetrafluoroethylene) also, and consistently observed adhesive failure, yielding IAS values consistent with literature reports, thereby validating the reliability of our test setup and adopted protocol. 12,13 Next, we replaced pure water with 1 wt% sodium chloride aqueous solution and froze it on the copper surface under the same conditions, and repeated the experiments to obtain IAS. Here, weight percentage refers to the mass ratio of the contaminant ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, understanding the fundamental mechanisms of ice adhesion to surfaces is crucial for developing effective de-icing technologies, improving materials with anti-icing properties, and ensuring safety in various fields, including aviation, energy production, transportation, and building design. 8,9 In this endeavor, several methods, including centrifugal and shear-removal 10–13 have been devised to measure the ice adhesion strength and then extensively used to study it on various surfaces such as common materials, non-wetting surfaces, oil-infused surfaces, gels etc. 11,14–19 A common element in all these studies is that the ice used in them was formed by freezing pure water.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, was no ice formation that obscured its visibility or affecting the composite film under sub-freezing conditions, contrasting with occurrences in other reported systems. 70 The thermal fading curves at different temperatures are reported in Figure 9b and reveal that the composite film CMC-5@15% can maintain its staining after irradiation with UV light for several weeks only if stored at temperatures below 4°C. Indeed, the film strips preserved at -19°C and 4°C have maintained a high staining (> 40%) even after 7 weeks The peak intensity at 470 nm recorded at t0 (film just irradiated) was considered as 100%, while that of the curve recorded after the complete fading of the staining (which overlaps that of the nonirradiated film) has been taken as 0%, as shown in Figure 10 Leveraging this property, we propose a labelling system incorporating photochromic film as a 'sensor' on product packaging or their containers (Figure 11).…”
Section: Photochromic Features In Composite Filmmentioning
confidence: 97%
“…16,17 Despite the bright application prospects of waxgels, 18-21 certain challenges remain. 22,23 For example, L. Jiang et al…”
mentioning
confidence: 99%
“…Despite the bright application prospects of waxgels, 18–21 certain challenges remain. 22,23 For example, L. Jiang et al reported a type of paraffin-based organogel material with a renewable sacrificial alkane surface layer, which was essentially a layer of wax that possessed excellent anti-icing properties. 24 However, the regeneration of the wax layer takes a long time at room temperature (>24 hours).…”
mentioning
confidence: 99%